Kisebbségi múlt és jövő Koszovóban - M. Császár, Zsuzsanna; Mérei, András; Végh, Andor (Közép-Európai Közlemények, 2009)
Kosovo as some international experts think could be the last post-jugoslavic country which has announced it’s independency. Despite Ahtisaari’s plan that provides even more rights to the serbs of Kosovo, the latest state of the Western-Balcan territory is permanently an ethnic conflict zone. Kosovo’s last 11 month shows ethnical tensions. The education also carries these tensions altough the constitutional frame allows the minority language education. Nowdays minority politics of Kosovo is an actually question and when the problems will be dissolved it could be a positive precedent for the Western-Balcan countries.